Sosialisasi Pentingnya Label Merek Pada Usaha Kelempang Tunu Mak Imam - Seto, Agung Anggoro (CV. IRA PUBLISHING, 2023)
One of the Small and Medium Enterprises in Palembang City is the Kelempang Tunu Mak Imam Business. Kelempang Tunu Mak Imam business has been established for more than 10 years, but even though it has been established for quite a long time, based on observations, this business still has several weaknesses, such as the lack of promotional facilities to increase sales results. This lack of promotional facilities is allegedly the reason why Kelempang Tunu Mak Imam business has not developed as expected. This community service activity aims to provide outreach regarding the importance of promotional tools to support business continuity and increase sales results. This community service activity uses primary data sourced from the results of primary interviews and observations with business actors as well as secondary data in the form of documents/studies related to service activities. The data analysis technique uses field studies, namely an analysis process that emphasizes the involvement of actors in service activities in various business activities of Kelempang Tunu Mak Imam. The activity stages include pre-activities, core activities and final activities (evaluation). The results of the activity concluded that the Tunu Mak Imam Lelempang Business has several weaknesses and threats such as the unavailability of promotional facilities, not yet keeping financial records (income and expenses) and the threat from similar products. However, Kelempang Tunu Mak Imam also has strengths and opportunities such as superior product types and flavors as well as open opportunities for collaboration with both banks and collaboration with other business actors. Apart from that, Kelempang Tunu Mak Imam business needs promotional facilities to increase the number of sales, one of the promotional means which is classified as economic which can be done is by making brand labels on the packaging.